THE INFLUENCE OF CYBERLOAFING AND HUSTLE CULTURE ON PERFORMANCE: MENTAL HEALTH AS MEDIATOR AMONG GEN Z EMPLOYEES - Nardi, Rio; Syahbandi, Syahbandi; Jaya, Arman; Fauzan, Rizky; Fahruna, Yulyanti (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2024)
The aim of this research is to explore whether there is a relationship between cyberloafing and hustle culture on the performance of Generation Z employees across Indonesia, mediated by mental health. Data was collected through a questionnaire distributed via Google Forms, with a total of 202 respondents. Structural Equation Modeling (SEM) and Partial Least Squares (PLS) were employed as data measurement methods, using the SMARTPLS 3 application. The findings indicate that cyberloafing negatively impacts mental health but not significantly affects employee performance. On the other hand, hustle culture significantly harms both mental health and employee performance. Mental health also have significant effect on employee performance. Additionally, both cyberloafing and hustle culture have a significant negative impact on performance, mediated by mental health. This research is expected to assist companies in designing more effective strategies to support employee well-being, understand the factors influencing the performance of Generation Z, and enrich the literature on human resource management, particularly concerning the relationship between mental health and performance.